Positive pole piece, battery, energy storage device and electric equipment
By using secondary particles formed by the fusion of primary particles in lithium iron phosphate batteries, the problem of difficulty in fully exerting the capacity performance of large-particle positive electrode materials is solved, and the battery capacity performance and cycling performance are improved.
Patent Information
- Application Number
- CN202510003020.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-15
AI Technical Summary
In high-pressure density lithium iron phosphate materials, the size of large particles is larger, increasing the lithium ion migration path, making it difficult to fully utilize the capacity performance of the positive electrode material.
Secondary particles formed by the fusion of primary particles are used. The surface of the second particle has gaps and holes inside. The holes are connected to the outside world through the gaps, which promotes rapid infiltration of the electrolyte and improves the diffusion capacity of lithium ions.
Effectively promote the capacity of large-particle positive electrode materials, improve the capacity and circulation performance of the battery, and reduce the elongation of the positive electrode sheet and extend the service life of the battery.
Smart Images

Figure CN119833550A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage technology, and in particular to a positive electrode sheet, a battery, an energy storage device and an electrical equipment. Background Art
[0002] Secondary batteries (such as lithium-ion batteries) have the characteristics of high specific energy, high operating voltage, low self-discharge rate, small size and light weight. They are widely used in various fields such as energy storage, portable electronic devices and electric vehicles.
[0003] Lithium-ion batteries based on lithium iron phosphate positive electrode materials have the advantages of high safety and stability. With the increasing requirements for battery capacity in energy storage scenarios, one of the main methods at present is to use lithium iron phosphate materials with high compaction density, and lithium iron phosphate materials mainly achieve high compaction density by increasing the proportion of large particles in the material. However, due to the large size of large particles (particle size is usually greater than 1μm), the lithium ion migration path will be increased, resulting in the capacity performance of the positive electrode material being difficult to fully exert. Therefore, in lithium iron phosphate materials with high compaction density, how to promote the full utilization of the material capacity of large particles has become a technical problem that needs to be solved urgently. Summary of the invention
[0004] In order to solve the above technical problems, the present application discloses a positive electrode plate, a battery, an energy storage device and an electrical equipment to promote the capacity of large-particle positive electrode materials and improve the capacity performance and cycle performance of the battery.
[0005] In a first aspect, the present application provides a positive electrode sheet, comprising a positive electrode current collector, wherein at least one side of the positive electrode current collector has a positive electrode material layer, wherein the positive electrode material layer comprises a positive electrode material, wherein the positive electrode material comprises a first particle and a second particle;
[0006] The second particles are secondary particles formed by fusion of the primary particles, the surfaces of the second particles have gaps, the interiors of the second particles have holes, and the holes are connected to the outside through the gaps;
[0007] The average sphericity of the second particles is S, where S≤0.6.
[0008] In some embodiments of the present application, 0.4≤S≤0.6.
[0009] In some embodiments of the present application, in the cross section of the second particle, the area of the holes accounts for A in the total area of the cross section, and 10%≤A≤23%.
[0010] In some embodiments of the present application, the second particle includes a plurality of fused primary particles, and the gap is located at the fused interface of the primary particles.
[0011] In some embodiments of the present application, the maximum particle size of the primary particles is D max , 1μm≤D max ≤6μm.
[0012] In some embodiments of the present application, the positive electrode material satisfies at least one of the following characteristics:
[0013] a) The Dv50 of the positive electrode material is D 1 , 0.8μm≤D 1 ≤1.3μm;
[0014] b) The compaction density of the positive electrode material is 2.5 g / cm 3 ~2.6g / cm 3 .
[0015] In some embodiments of the present application, the first particle has a solid ellipsoidal structure.
[0016] In some embodiments of the present application, the Dv50 of the first particle is D 2 , 0.2μm≤D 2 ≤0.5μm.
[0017] In some embodiments of the present application, the positive electrode material has a chemical formula of LiFe x Ti y PO 4 / C, x+y=1, and 0<y≤0.05.
[0018] In some embodiments of the present application, the elongation of the positive electrode sheet is 0.5% to 0.8%.
[0019] In a second aspect, the present application provides a battery, comprising the positive electrode plate described in the first aspect.
[0020] In a third aspect, the present application provides an energy storage device, comprising a housing and at least one battery as described in the second aspect, wherein the battery is accommodated in the housing.
[0021] In a fourth aspect, the present application provides an electrical device, comprising the energy storage device described in the third aspect, wherein the energy storage device supplies power to the electrical device.
[0022] Compared with the prior art, this application has at least the following beneficial effects:
[0023] The present application provides a positive electrode sheet, a battery, an energy storage device and an electrical device, wherein the positive electrode sheet includes a positive electrode current collector, at least one side of the positive electrode current collector has a positive electrode material layer, the positive electrode material layer includes a positive electrode material, and the positive electrode material includes a first particle and a second particle, wherein the second particle is a secondary particle formed by the fusion of primary particles, the surface of the second particle has a gap, the interior of the second particle has a hole, and the hole is connected to the outside through the gap, which can promote the electrolyte to quickly infiltrate the positive electrode material through the gap and the hole, improve the lithium ion diffusion capacity, thereby promoting the capacity of the large-particle positive electrode material therein, and the secondary particles formed by the fusion of the primary particles are block-shaped as a whole, have higher mechanical strength, and are less likely to break during the battery cycle, thereby improving the battery cycle performance; the average sphericity of the second particle is S, S≤0.6, and has a lower sphericity, which can hinder the displacement and deformation of the particles during rolling, thereby reducing the elongation of the positive electrode sheet. In summary, the present application can improve the capacity performance and cycle performance of the secondary battery, and the positive electrode sheet has a lower elongation. When the secondary battery of the present application is applied to an energy storage device, the energy storage efficiency and service life of the energy storage device are improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 A schematic diagram of the structure of a household energy storage system according to an implementation scheme of the present application;
[0026] Figure 2 A schematic diagram of the structure of a commercial energy storage system according to an implementation scheme of the present application;
[0027] Figure 3 A schematic diagram of the elongation test of the positive electrode sheet of this application;
[0028] Figure 4 is a scanning electron microscope (SEM) image of the positive electrode material of Example 1;
[0029] Figure 5 This is a SEM image of the positive electrode material of Comparative Example 1;
[0030] Figure 6 This is a SEM image of the positive electrode material of Comparative Example 2;
[0031] Figure 7 is a SEM image of the cross section of the positive electrode material layer of Example 1;
[0032] Figure 8 is a partial SEM enlarged view of the cross section of the positive electrode material layer of Example 1;
[0033] Fig. 9 This is a partial SEM enlarged view of the cross section of the positive electrode material layer of Comparative Example 1;
[0034] Fig.10 1 is a particle size distribution diagram of the positive electrode materials of Example 1, Comparative Example 1 and Comparative Example 2.
[0035] Explanation of the accompanying drawings: 1-energy storage device, 2-electric energy conversion device, 3-first user load, 4-second user load, 11-positive electrode current collector, 12-first positive electrode material layer, 13-second positive electrode material layer, 40-roller, 400-commercial energy storage system, 410-high voltage cable, 420-first electric energy conversion device, 430-second electric energy conversion device. DETAILED DESCRIPTION
[0036] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0037] In the present application, the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "vertical", "horizontal", "lateral", "longitudinal" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings. These terms are mainly used to better describe the present application and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific orientation, or to be constructed and operated in a specific orientation.
[0038] In addition, some of the above terms may be used to express other meanings in addition to indicating orientation or positional relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those of ordinary skill in the art, the specific meanings of these terms in this application can be understood according to specific circumstances.
[0039] In addition, the terms "installed", "set", "provided with", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be an internal connection between two devices, elements, or components. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0040] In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.
[0041] It should be noted that, in the present application, a lithium-ion battery is used as an example of a secondary battery to explain the present application, but the secondary battery of the present application is not limited to a lithium-ion battery.
[0042] In order to improve the compaction density of the positive electrode material, lithium iron phosphate materials usually adopt a two-level gradation of large and small particles, that is, small particles are mainly used, with a certain degree of large particles. However, if the size of the large particles is large, it will increase the migration path of lithium ions, making it difficult to fully exert its capacity performance. In addition, if the particle size of the primary particles that constitute the large particles is too small (for example, nano-scale particles), although the capacity of the large particle material can be improved, there is a problem of low overall mechanical strength of the large particles. When the positive electrode sheet is rolled or during the charge and discharge cycle, the large particles are prone to breakage, affecting the cycle performance of the lithium-ion battery.
[0043] In view of this, the present application provides a positive electrode plate, which includes a positive electrode current collector, at least one side of the positive electrode current collector has a positive electrode material layer, the positive electrode material layer includes a positive electrode material, the positive electrode material includes a first particle and a second particle, the second particle is a secondary particle formed by the fusion of primary particles, the surface of the second particle has a gap, the interior of the second particle has a hole, and the hole is connected to the outside through the gap. In the positive electrode material of the present application, the first particle is a primary particle; the second particle is a secondary particle. The average sphericity of the second particle is S, S≤0.6; in another optional embodiment, 0.4≤S≤0.6. For example, S is 0.4, 0.45, 0.5, 0.55 or 0.6.
[0044] The positive electrode sheet of the present application contains the above-mentioned positive electrode material, wherein the second particle has holes inside, and the holes are connected to the outside through the gap, which can promote the electrolyte to quickly infiltrate the positive electrode material through the gap and the hole, improve the diffusion capacity of lithium ions, and thus promote the capacity of the large-particle positive electrode material therein, and the secondary particles formed by the fusion of the primary particles are block-shaped as a whole, have higher mechanical strength, and are less likely to break during the cycle of the lithium-ion battery, thereby improving the cycle performance of the lithium-ion battery; the inventors have found that when S is too large (for example, greater than 0.6), the second particles are more inclined to present a spherical structure, which is more likely to be displaced and deformed during rolling, which is not conducive to reducing the elongation of the positive electrode sheet; S should not be too small, otherwise it may affect the compaction density of the positive electrode material, which is not conducive to the capacity of the positive electrode material. The second particles of the present application have a lower sphericity, which can hinder the displacement and deformation of the particles during rolling, thereby reducing the elongation of the positive electrode sheet. In summary, the present application can improve the capacity performance and cycle performance of lithium-ion batteries, and the positive electrode sheet has a lower elongation. When the lithium-ion battery of the present application is applied to an energy storage device, the energy storage efficiency and service life of the energy storage device are improved.
[0045] In the present application, sphericity refers to the ratio of the major diameter to the minor diameter of a particle.
[0046] In an optional embodiment, in the cross section of the second particle, the area of the pores accounts for A in the total area of the cross section, 10%≤A≤23%; in another optional embodiment, 10%≤A≤15%. For example, A is 10%, 12%, 13%, 15%, 18%, 20% or 23%. By regulating the value of A within the above range, the positive electrode material can have good electrolyte wettability and sufficient mechanical strength, which is beneficial to improving the capacity performance and cycle performance of lithium-ion batteries.
[0047] In an optional embodiment, the second particle includes a plurality of fused primary particles, and the gap is located at the fusion interface of the fused primary particles, so that the surface of the second particle presents a "splicing" structure, that is, the second particle is formed by splicing a plurality of primary particles after fusion, which is beneficial for the electrolyte to enter the interior of the second particle through the gap, thereby improving the capacity performance of the positive electrode material.
[0048] In an optional embodiment, the maximum particle size of the primary particles is D max , 1μm≤D max ≤6μm; in another optional embodiment, 1.4μm≤D max ≤3μm. For example, D max 1μm, 1.3μm, 1.5μm, 1.8μm, 2.5μm, 3μm, 4μm, 5μm or 6μm. By adjusting D maxWithin the above range, it is beneficial to promote the surface of the second particle to present a "splicing" structure, thereby forming a gap at the fusion interface of the primary particle after fusion, which is beneficial for the electrolyte to enter the interior of the second particle through the gap, thereby improving the capacity performance of the positive electrode material.
[0049] In an optional embodiment, the Dv50 of the positive electrode material is D 1 , 0.8μm≤D 1 ≤1.3μm; in another optional embodiment, 0.9μm≤D 1 ≤1.2μm. For example, D 1 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm or 1.3μm. By adjusting D 1 Within the above range, it is beneficial to achieve a more reasonable particle size distribution of the first particles and the second particles, thereby reducing the elongation of the positive electrode sheet while improving the capacity of the positive electrode sheet.
[0050] In the present application, Dv50 means a particle size at which the volume accumulation is 50% from the smaller particle size side in a volume-based particle size distribution of particles.
[0051] In an optional embodiment, the compaction density of the positive electrode material is 2.5 g / cm 3 ~2.6g / cm 3 By adjusting the compaction density of the positive electrode material layer within the above range, it is beneficial to exert the capacity performance of the lithium-ion battery.
[0052] In an optional embodiment, the first particle has a solid ellipsoidal structure, which can make the positive electrode material have a higher compaction density, which is beneficial to improving the capacity of the lithium-ion battery.
[0053] In an optional embodiment, the Dv50 of the first particle is D 2 , 0.2μm≤D 2 ≤0.5μm. For example, D 2 The diameter of the second particle is 0.2 μm, 0.3 μm, 0.4 μm or 0.5 μm. In this way, the second particle can form a two-level gradation of large and small particles, so that the positive electrode material has a higher compaction density, which is beneficial to improving the capacity of the lithium ion battery.
[0054] In an alternative embodiment, the positive electrode material has the chemical formula LiFe x Ti y PO 4 / C, x+y=1, and 0<y≤0.05, for example, y=0.01, 0.02, 0.03, 0.04 or 0.05. The positive electrode material having the above chemical formula contains doping element titanium (Ti), which can provide more capacity and is conducive to improving the capacity performance of lithium ion batteries.
[0055] In an optional embodiment, the elongation of the positive electrode sheet is 0.5% to 0.8%, for example, the elongation is 0.5%, 0.6%, 0.7% or 0.8%. Therefore, it has a lower elongation, which is beneficial to reduce the risk of cracking at the edge of the positive electrode sheet and improve the yield of lithium-ion batteries.
[0056] In an optional embodiment, the method for preparing the positive electrode material comprises the following steps:
[0057] Preparation of the first pre-sintered material:
[0058] Step a: According to LiFe x Ti y PO 4 / C (x+y=1, and 0<y≤0.05) as the first raw material; then weighing a carbon source according to 15% to 25% of the total mass of the first raw material as the second raw material; uniformly mixing the first raw material and the second raw material on a ball mill, adding pure water as a dispersant, and then performing high-energy ball milling;
[0059] Step b, spray drying the material after high-energy ball milling to form a first powder;
[0060] Step c: placing the first powder into a vacuum atmosphere sintering furnace for a first sintering treatment, and then crushing the first powder to obtain a first pre-sintered material.
[0061] Preparation of the second pre-sintered material:
[0062] Step a', according to LiFe x Ti y PO 4 / C (x+y=1, and 0<y≤0.05) in the required stoichiometric ratio, weighing an iron source, a phosphorus source, a lithium source and a titanium source as the third raw material; then weighing a carbon source according to 12% to 18% of the total mass of the first raw material as the fourth raw material; uniformly mixing the third raw material and the fourth raw material on a ball mill, adding pure water as a dispersant, and then performing high-energy ball milling;
[0063] Step b', spray drying the material after high-energy ball milling to form a second powder;
[0064] Step c', placing the second powder into a vacuum atmosphere sintering furnace for a second sintering treatment, and then crushing the second powder to obtain a second pre-sintered material.
[0065] Preparation of positive electrode materials:
[0066] The first pre-sintered material and the second pre-sintered material are mixed in a mass ratio of (6-8):(2-4), and then placed in a vacuum atmosphere sintering furnace for a third sintering treatment, and then crushed to obtain a positive electrode material.
[0067] In step a or a', the iron source can be selected from ferrous oxalate, ferric phosphate or ferric oxide, the phosphorus source can be selected from lithium dihydrogen phosphate or ammonium dihydrogen phosphate, the lithium source can be selected from lithium carbonate or lithium hydroxide, and the titanium source can be selected from titanium dioxide; the carbon source can be selected from glucose, sucrose or citric acid; the ball-to-material ratio of high-energy ball milling is 3 to 5:1, the rotation speed is 1000 r / min to 1500 r / min, and the ball milling time is 15 h to 20 h.
[0068] In step b or b', the pump speed of spray drying is 8 mL / min to 12 mL / min, the drying temperature is 180° C. to 220° C., and the formed powder is granular.
[0069] In step c, the protective atmosphere is nitrogen, the temperature of the first sintering treatment is 340° C. to 360° C., and the sintering time is 5 h to 10 h.
[0070] In step c', the protective atmosphere is nitrogen, the temperature of the second sintering treatment is 440° C. to 520° C., and the sintering time is 6 h to 15 h.
[0071] In the positive electrode material preparation step, the protective atmosphere is nitrogen, the third sintering temperature is 690° C. to 710° C., and the sintering time is 8 h to 12 h.
[0072] The present application has no particular restrictions on the method of regulating the average sphericity of the second particles, as long as the purpose of the present application can be achieved. For example, the average sphericity of the second particles usually decreases with the reduction of the carbon source content in the second pre-sintered material. Based on this, the present application can regulate the average sphericity of the second particles by regulating the content of the carbon source in the second pre-sintered material. For another example, the average sphericity of the second particles usually decreases with the increase of the sintering temperature during the second sintering treatment. Based on this, the present application can regulate the average sphericity of the second particles by regulating the temperature of the second sintering treatment. For another example, the average sphericity of the second particles usually decreases with the increase of the sintering time during the second sintering treatment. Based on this, the present application can regulate the average sphericity of the second particles by regulating the sintering time of the second sintering treatment.
[0073] The present application does not particularly limit the method of regulating the A value, as long as the purpose of the present application can be achieved. For example, the A value usually increases with the decrease of the carbon source content in the second pre-sintered material. Based on this, the present application can regulate the A value by regulating the content of the carbon source in the second pre-sintered material. For another example, the A value usually increases with the increase of the sintering temperature during the second sintering treatment. Based on this, the present application can regulate the A value by regulating the temperature of the second sintering treatment. For another example, the A value usually increases with the increase of the sintering time during the second sintering treatment. Based on this, the present application can regulate the A value by regulating the sintering time of the second sintering treatment.
[0074] This application regulates D max There is no particular limitation on the method, as long as the purpose of this application can be achieved. max Generally, it increases with the decrease of the carbon source content in the second pre-sintered material. Based on this, the present application can adjust D by adjusting the content of the carbon source in the second pre-sintered material. max For another example, D max Generally, it increases with the increase of the sintering temperature during the second sintering process. Based on this, the present application can adjust D by adjusting the temperature of the second sintering process. max For another example, D max Generally, it increases with the increase of the sintering time in the second sintering process. Based on this, the present application can adjust D by adjusting the sintering time of the second sintering process. max .
[0075] The present application also provides a battery, comprising the positive electrode sheet described in any of the above embodiments.
[0076] In the present application, the positive electrode material layer can be arranged on one surface in the thickness direction of the positive electrode current collector, or on two surfaces in the thickness direction of the positive electrode current collector. In the present application, the positive electrode material layer is arranged on the surface of the positive electrode current collector, that is, the positive electrode material layer can be arranged in a partial area of one surface of the positive electrode current collector, or in the entire area of one surface of the positive electrode current collector. In the present application, there is no special restriction on the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, it can include but is not limited to aluminum foil, aluminum alloy foil or composite current collector. In the present application, there is no special restriction on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness is 4μm to 12μm. The single-sided thickness of the positive electrode material layer of the present application can be 8μm to 15μm.
[0077] The lithium-ion battery of the present application also includes a negative electrode sheet. The present application has no special restrictions on the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the negative electrode sheet generally includes a negative electrode collector and a negative electrode material layer. The negative electrode material layer can be arranged on one surface or two surfaces along the thickness direction of the negative electrode collector. In the present application, the negative electrode material layer is arranged on the surface of the negative electrode collector, that is, the negative electrode material layer can be arranged in a partial area of one surface of the negative electrode collector, or in the entire area of one surface of the negative electrode collector. The present application has no special restrictions on the negative electrode collector, as long as the purpose of the present application can be achieved. For example, it can include but is not limited to copper foil, copper alloy foil, nickel foil or composite current collector. In the present application, there is no special restriction on the thickness of the negative electrode collector, as long as the purpose of the present application can be achieved, for example, the thickness is 4μm to 12μm. The single-sided thickness of the negative electrode material layer of the present application can be 70μm to 200μm.
[0078] In the present application, the negative electrode material layer includes a negative electrode material, wherein the negative electrode material is not particularly limited as long as the purpose of the present application can be achieved. For example, it may include at least one of artificial graphite, natural graphite, mesophase carbon microbeads, soft carbon, hard carbon, silicon, and silicon carbon.
[0079] In the present application, the negative electrode material layer may further include a negative electrode binder. The present application has no particular restrictions on the negative electrode binder, as long as it can achieve the purpose of the present application, for example, it may include but is not limited to at least one of acrylate, polyamide, polyimide, polyamideimide, polyvinylidene fluoride, styrene-butadiene rubber, sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile, sodium carboxymethyl cellulose, and potassium carboxymethyl cellulose.
[0080] The lithium-ion battery of the present application also includes a diaphragm. The present application has no particular restrictions on the diaphragm, and those skilled in the art can select it according to actual needs, as long as the purpose of the present application can be achieved. For example, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film can be selected.
[0081] The battery of the present application also includes an electrolyte. The present application has no particular restrictions on the electrolyte, and those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved. For example, at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl propionate (EP), propyl propionate (PP), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), vinylene carbonate (VC) or fluoroethylene carbonate (FEC) is mixed in a certain mass ratio or volume ratio to obtain a non-aqueous organic solvent, and then a lithium salt is added to dissolve and mix evenly. The present application has no restrictions on the type of lithium salt, as long as the purpose of the present application can be achieved. For example, the lithium salt may include LiPF 6 , LiBF 4 、LiAsF 6 、LiClO 4 、LiB(C 6 H 5 ) 4 、LiCH 3 SO 3 、LiCF 3 SO 3 、LiN(SO 2 CF 3 ) 2 、LiC(SO 2 CF 3 ) 3 、LiSiF 6 , lithium bis(oxalatoborate) (LiBOB) or lithium difluoroborate.
[0082] The present application has no particular limitation on the concentration of lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. 6 For example, LiPF 6 The concentration in the electrolyte is 5wt% to 25wt%, for example, LiPF 6 The concentration is 5wt%, 10wt%, 11wt%, 12wt%, 12.5wt%, 15wt%, 20wt% or 25wt%.
[0083] The battery of the present application also includes a shell, and the present application has no particular limitation on the shell, and those skilled in the art can select it according to actual needs, as long as the purpose of the present application can be achieved. For example, the shell may include an aluminum-plastic film.
[0084] The present application does not particularly limit the preparation method of the battery, and a preparation method known in the art can be selected as long as the purpose of the present application can be achieved. For example, the preparation method of the battery includes but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain a bare cell with a wound structure, placing the bare cell in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a battery.
[0085] The present application also provides an energy storage device, including a housing and at least one battery in any of the above embodiments, wherein the battery is contained in the housing. The energy storage device having the battery has excellent performance, which is beneficial to the use of the energy storage device. By containing the battery in the housing, the fixation and protection of the battery can be increased, thereby improving the service life of the energy storage device. It is understandable that the energy storage device may have one or more batteries, and when the energy storage device contains multiple batteries, the multiple batteries may be connected in at least one of parallel and series connection.
[0086] The present application also provides an electrical device, including the energy storage device in the above-mentioned implementation scheme, which is conducive to improving the product competitiveness and performance of the electrical device. In an optional implementation scheme, the electrical device includes an electrical device body, and the energy storage device is used to supply power to the electrical device body. In an optional implementation scheme, the electrical device body includes a positive electrode of the device and a negative electrode of the device, the positive electrode plate of the battery in the energy storage device is used to electrically connect to the positive electrode of the device body of the electrical device, and the negative electrode plate of the battery in the energy storage device is used to electrically connect to the negative electrode of the device body of the electrical device, so as to supply power to the electrical device.
[0087] The electrical equipment of the present application may include but is not limited to: containers, battery vehicles, electric vehicles, ships, spacecraft, electric toys and electric tools, etc., wherein spacecrafts include airplanes, rockets, space shuttles and spacecrafts, etc., electric toys include fixed or mobile electric toys, such as electric car toys, electric ship toys and electric airplane toys, etc., and electric tools include metal cutting power tools, grinding power tools, assembly power tools and railway power tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers.
[0088] See also Figure 1 , Figure 1 This is a schematic diagram of the structure of a household energy storage system according to an implementation scheme of the present application, and the present application Figure 1 The implementation plan is described using a household energy storage scenario in user-side energy storage as an example, but the energy storage device of the present application is not limited to the household energy storage scenario.
[0089] The present application provides a household energy storage system, which includes an energy conversion device 2 (photovoltaic panel), a first user load 3 (street lamp), a second user load 4 (such as air conditioner and other household appliances), and an energy storage device 1. The energy storage device 1 is a small energy storage box that can be mounted on an outdoor wall by wall hanging. Specifically, the photovoltaic panel can convert solar energy into electrical energy during the period of low electricity prices. The energy storage device 1 is used to store the electrical energy and supply it to street lamps and household appliances for use during the peak electricity prices, or to supply power when the power grid is out of power / power outage.
[0090] See also Figure 2 , Figure 2 A schematic diagram of a commercial energy storage system 400 according to an embodiment of the present application. Figure 2 The implementation plan is described using the shared energy storage scenario on the generation / distribution side as an example, and the energy storage device 1 of the present application is not limited to the energy storage scenario on the generation / distribution side.
[0091] The present application provides a commercial energy storage system 400, which includes: a high-voltage cable 410, a first electric energy conversion device 420, a second electric energy conversion device 430 and an energy storage device 1 provided in the present application. In the case of power generation, the first electric energy conversion device 420 and the second electric energy conversion device 430 are used to convert other forms of energy into electric energy, which are connected to the high-voltage cable 410 and supplied to the power distribution network for use. When the power load is low and the first electric energy conversion device 420 and the second electric energy conversion device 430 generate excess power, the excess power is stored in the energy storage device 1, thereby reducing the wind and solar power abandonment rates and improving the problem of new energy power generation and consumption. When the power load is high, the power grid issues an instruction to transmit the power stored in the energy storage device 1 in conjunction with the high-voltage cable 410 in a grid-connected mode to the power consumption side, thereby providing peak load regulation, frequency regulation, standby and other services for the power grid operation, giving full play to the peak load regulation of the power grid, promoting peak load shaving and valley filling of the power grid, and alleviating the power supply pressure of the power grid.
[0092] Optionally, the first electric energy conversion device 420 and the second electric energy conversion device 430 can convert at least one of solar energy, light energy, wind energy, thermal energy, tidal energy, biomass energy and mechanical energy into electric energy.
[0093] The number of energy storage devices 1 can be multiple, and multiple energy storage devices 1 are connected in series or in parallel. Multiple energy storage devices 1 are supported and electrically connected by isolation plates (not shown). In this embodiment, "multiple" refers to two or more. An energy storage box can also be provided outside the energy storage device 1 to accommodate the energy storage device 1.
[0094] Optionally, the energy storage device 1 may include but is not limited to a battery module, a battery pack, a battery system, etc. Among them, the battery module may be a battery module formed by connecting multiple batteries of the present application in series / parallel, the battery pack may include multiple batteries of the present application, and the battery system may be a charging and discharging system including the battery or battery pack of the present application.
[0095] The actual application form of the energy storage device 1 provided in the embodiment of the present application may be, but is not limited to, the listed products, and may also be other application forms. The embodiment of the present application does not strictly limit the application form of the energy storage device 1. The embodiment of the present application only takes the energy storage device 1 as a multi-core battery as an example for explanation. When the energy storage device 1 includes a single cell, the single cell may be at least one of a cylindrical battery, a square battery, and the like.
[0096] The positive electrode sheet, battery, energy storage device and electrical equipment of the present application are further described below in conjunction with more specific embodiments.
[0097] Example
[0098] Hereinafter, the embodiments of the present application will be described in more detail with reference to preparation examples, examples and comparative examples. Various tests and evaluations were performed according to the following methods.
[0099] Example 1
[0100] <Preparation of positive electrode sheet>
[0101] <Preparation of the first calcined material>
[0102] According to LiFe 0.99 Ti 0.01 PO 4 / C according to the required stoichiometric ratio as the first raw material, iron source ferrous oxalate, phosphorus source lithium dihydrogen phosphate, lithium source lithium carbonate and titanium source titanium dioxide; then weigh 20% of the total mass of the first raw material as the carbon source glucose; the first raw material and the second raw material are evenly mixed in a ball mill, pure water is added as a dispersant, and then high-energy ball milling is performed, the ball-to-material ratio of the high-energy ball milling is 4:1, the rotation speed is 1500r / min, and the ball milling time is 20h; the material after high-energy ball milling is spray-dried, the pump speed of the spray drying is 10mL / min, and the drying temperature is 200℃ to form a first powder; the first powder is placed in a vacuum atmosphere sintering furnace for a first sintering treatment, the protective atmosphere is nitrogen, the sintering temperature is 350℃, the sintering time is 6h, and after ball milling and crushing, a first pre-sintered material is obtained.
[0103] <Preparation of the Second Pre-sintered Material>
[0104] According to LiFe 0.99 Ti 0.01 PO 4 / C, weighing ferrous oxalate as an iron source, lithium dihydrogen phosphate as a phosphorus source, lithium carbonate as a lithium source and titanium dioxide as a titanium source in the required stoichiometric ratio as the third raw material; then weighing glucose as a carbon source according to 18% of the total mass of the first raw material as a fourth raw material; the third raw material and the fourth raw material are uniformly mixed in a ball mill, and then pure water is added as a dispersant, and then high-energy ball milling is performed, the ball-to-material ratio of the high-energy ball milling is 4:1, the rotation speed is 1500r / min, and the ball milling time is 20h; the material after high-energy ball milling is spray-dried, the pump speed of the spray drying is 10mL / min, and the drying temperature is 200℃ to form a second powder; the second powder is placed in a vacuum atmosphere sintering furnace for a second sintering treatment, the protective atmosphere is nitrogen, the sintering temperature and the sintering time are as shown in Table 1, and after ball milling and crushing, a second pre-sintered material is obtained.
[0105] <Preparation of positive electrode material>
[0106] The first pre-burned material and the second pre-burned material were mixed in a mass ratio of 7:3, and then placed in a vacuum atmosphere sintering furnace for a third sintering treatment. The protective atmosphere was nitrogen, the sintering temperature was 700°C, the sintering time was 10 hours, and the positive electrode material was obtained after crushing treatment.
[0107] <Preparation of positive electrode material layer>
[0108] The prepared positive electrode material, conductive carbon black (Super-P), and binder PVDF are mixed in a mass ratio of 95:2:3, and then N-methylpyrrolidone (NMP) is added as a solvent to prepare a positive electrode slurry with a solid content of 50wt%, and stirred evenly. Then, the positive electrode slurry is evenly coated on one surface of a positive electrode collector with a thickness of 10μm, dried at 85°C, and then the above steps are repeated on the other surface of the positive electrode sheet. After rolling, a positive electrode sheet coated with a positive electrode material layer on both sides is obtained, and the single-side thickness of the positive electrode material layer is 100μm.
[0109] <Preparation of negative electrode sheet>
[0110] The negative electrode materials artificial graphite, conductive carbon black (Super-P) and sodium carboxymethyl cellulose (CMC-Na) were mixed in a mass ratio of 95:2.5:2.5, deionized water was added, and a negative electrode slurry with a solid content of 60wt% was prepared, and stirred evenly. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 10μm, dried at 85℃, and then the above steps were repeated on the other surface of the negative electrode sheet. After rolling, a negative electrode sheet with a negative electrode material layer coated on both sides was obtained, and the single-side thickness of the negative electrode material layer was 70μm.
[0111] <Preparation of Electrolyte>
[0112] Ethylene carbonate (EC) and diethyl carbonate (DEC) were mixed in a volume ratio of 1:1, dissolved and stirred thoroughly, and then placed in an environment of 5°C or less for 12 hours, and then lithium salt LiPF was added. 6 , and mix well to obtain an electrolyte. Among them, LiPF 6 The concentration in the electrolyte is 12.5 wt%.
[0113] <Preparation of Separator>
[0114] A polyethylene (PE) porous polymer film with a thickness of 16 μm was used as the separator.
[0115] <Assembly of lithium-ion batteries>
[0116] The prepared positive electrode sheet and negative electrode sheet are respectively placed in a press for pressing, and then a puncher is used to cut out a circular positive electrode sheet with a diameter of 15 mm and a circular negative electrode sheet with a diameter of 18 mm respectively; then the circular positive electrode sheet, the diaphragm and the circular negative electrode sheet are stacked in order, so that the diaphragm is placed between the circular positive electrode sheet and the circular negative electrode sheet to play an isolating role, and then the prepared electrolyte is injected to assemble into a lithium-ion battery.
[0117] Embodiment 2 to Embodiment 4
[0118] Except that the amount of the carbon source added is adjusted according to Table 1 in the preparation of the second pre-sintered material, the rest is the same as that of Example 1.
[0119] Embodiment 5 to Embodiment 13
[0120] Except that the sintering temperature and sintering time of the second sintering treatment are adjusted according to Table 1 in <Preparation of the Second Pre-sintered Material>, the rest is the same as Example 1.
[0121] Embodiment 14
[0122] Except in <Preparation of the First Pre-sintered Material> and <Preparation of the Second Pre-sintered Material>, according to LiFe 0.98 Ti 0.02 PO 4 Except for weighing each raw material in the required stoichiometric ratio in / C, the rest is the same as Example 1.
[0123] Embodiment 15
[0124] Except in <Preparation of the First Pre-sintered Material> and <Preparation of the Second Pre-sintered Material>, according to LiFe 0.97 Ti 0.03 PO 4 Except for weighing each raw material in the required stoichiometric ratio in / C, the rest is the same as Example 1.
[0125] Example 16
[0126] Except in <Preparation of the First Pre-sintered Material> and <Preparation of the Second Pre-sintered Material>, according to LiFe 0.96 Ti 0.04 PO 4 Except for weighing each raw material in the required stoichiometric ratio in / C, the rest is the same as Example 1.
[0127] Embodiment 17
[0128] Except in <Preparation of the First Pre-sintered Material> and <Preparation of the Second Pre-sintered Material>, according to LiFe 0.95 Ti 0.05 PO 4 Except for weighing each raw material in the required stoichiometric ratio in / C, the rest is the same as Example 1.
[0129] Comparative Example 1
[0130] Except that the positive electrode material used in <Preparation of positive electrode sheet> is different from that in Example 1, the rest is the same as Example 1. The steps for preparing the positive electrode material are as follows:
[0131] According to LiFe 0.99 Ti 0.01 PO 4 / C, weighing ferrous oxalate as an iron source, lithium dihydrogen phosphate as a phosphorus source, lithium carbonate as a lithium source and titanium dioxide as a titanium source in the required stoichiometric ratio as the first raw material; then weighing glucose as a carbon source according to 20% of the total mass of the first raw material as the second raw material; the first raw material and the second raw material are evenly mixed in a ball mill, and then pure water is added as a dispersant, and then high-energy ball milling is performed, the ball-to-material ratio of the high-energy ball milling is 4:1, the rotation speed is 1500r / min, and the ball milling time is 20h; the material after high-energy ball milling is spray-dried, the pump speed of the spray drying is 10mL / min, and the drying temperature is 200℃ to form a powder; the powder is placed in a vacuum atmosphere sintering furnace for sintering treatment, the protective atmosphere is nitrogen, the sintering temperature is 700℃, the sintering time is 10h, and after ball milling and crushing treatment, the positive electrode material is obtained.
[0132] Comparative Example 2
[0133] Except that the positive electrode material used in <Preparation of positive electrode sheet> is different from that in Example 1, the rest is the same as Example 1. The steps for preparing the positive electrode material are as follows:
[0134] According to LiFe 0.99 Ti 0.01 PO 4 / C, weighing ferrous oxalate as an iron source, lithium dihydrogen phosphate as a phosphorus source, lithium carbonate as a lithium source and titanium dioxide as a titanium source in the required stoichiometric ratio as the first raw material; then weighing glucose as a carbon source according to 25% of the total mass of the first raw material as the second raw material; the first raw material and the second raw material are evenly mixed in a ball mill, and then pure water is added as a dispersant, and then high-energy ball milling is performed, the ball-to-material ratio of the high-energy ball milling is 4:1, the rotation speed is 15000r / min, and the ball milling time is 20h; the material after high-energy ball milling is spray-dried, the pump speed of the spray drying is 10mL / min, and the drying temperature is 200℃ to form a powder; the powder is placed in a vacuum atmosphere sintering furnace for sintering treatment, the protective atmosphere is nitrogen, the sintering temperature is 600℃, the sintering time is 10h, and after ball milling and crushing treatment, the positive electrode material is obtained.
[0135] Table 1: Preparation parameters of Examples 1 to 13
[0136]
[0137]
[0138] In Table 1, “ / ” indicates that there is no relevant preparation parameter.
[0139] Test methods and equipment:
[0140] Average sphericity test:
[0141] The sphericity results of 50 second particles with a particle size ≥ 1 μm were counted by SEM at 3K magnification, and then the average value was calculated, which was the average sphericity of the second particles.
[0142] The maximum particle size D in primary particles max Determination of:
[0143] Randomly select five SEM images of the positive electrode material taken at 3K magnification, find a primary particle with the longest diameter from the second particles in the five SEM images, and use the diameter of the primary particle as D max .
[0144] Hole area ratio test:
[0145] The positive electrode sheet was cut using a focused ion beam, and then the cross-sectional distribution of the second particles in the positive electrode material layer was observed using a SEM, with a shooting magnification of 5K. The sum of the areas of the holes of 100 second particles was measured using ImageJ software, recorded as S 1 , and the total area of 100 second particles, denoted as S 总 , then the value of the hole area ratio A is [(S 1 / S 总 ) / 100]×100%.
[0146] Material particle size distribution test:
[0147] The particle size distribution of the positive electrode material and the first particle was measured using a laser diffraction particle size distribution measuring instrument (Malvern Mastersizer 3000) according to the particle size distribution laser diffraction method (GB / T19077-2016), thereby measuring the Dv50 of the positive electrode material and the Dv50 of the first particle.
[0148] Positive electrode elongation test:
[0149] like Figure 3 As shown, the positive electrode sheet includes a positive electrode current collector 11, a first positive electrode material layer 12 and a second positive electrode material layer 13. Before rolling, two points A and B are marked on the surface of the first positive electrode material layer 12 or the surface of the second positive electrode material layer 13. 1 is the distance between points A and B before the positive electrode sheet is rolled; after being rolled by the roller 40, the positive electrode sheet will extend along its length direction, and the distance between points A and B will be lengthened, that is, the distance from A' to B', recorded as L 2 . Calculate the pole piece elongation rate: (L 2 -L 1 ) / L 1 ×100%.
[0150] Rate performance test:
[0151] The test temperature is 25°C. The lithium-ion battery is charged to 3.65V at a rate of 0.1 (C), and then discharged to 2.5V at a rate of 0.1C. The 0.1C discharge capacity is recorded in mAh / g.
[0152] Cycle performance test:
[0153] The test temperature is 25℃. The lithium-ion battery is charged to 3.65V at 1C constant current, and then discharged to 2.5V at 1C after standing for 10 minutes. The capacity obtained in this step is the initial discharge capacity C 0 , perform 200 cycles of 1C charge / 1C discharge, and record the discharge capacity at the 200th cycle. Cycle capacity retention rate = (200th cycle discharge capacity / initial discharge capacity C 0 )×100%.
[0154] Table 2: Related parameters of the positive electrode materials of various embodiments and comparative examples
[0155]
[0156]
[0157] Table 3: Performance data of various embodiments and comparative examples
[0158]
[0159] It can be seen from Examples 1 to 17 and Comparative Examples 1 and 2 that although the capacity retention rate of Comparative Example 1 is relatively high, its positive electrode sheet elongation rate is relatively high, and the 0.1C discharge capacity is relatively low. This may be due to the positive electrode material of Comparative Example 1, in which the small particles have been completely fused into large particles, resulting in no gaps on the surface of the large particles and a solid structure formed inside. Although this structure is beneficial to improving the mechanical strength of the material, it is not conducive to electrolyte infiltration, and it is difficult to prevent the particles from being displaced and deformed after being compressed, resulting in an increase in the elongation of the positive electrode sheet and limited capacity. The 0.1C discharge capacity and capacity retention rate of Comparative Example 2 are both low, and the elongation rate of the positive electrode sheet is relatively high. This may be due to the positive electrode material of Comparative Example 2, in which the small particles are nanometer-sized, so that the large particles formed form a loose porous structure. Although this structure is beneficial to electrolyte infiltration, it is not conducive to improving the mechanical strength of the material. The particles are fractured during rolling, and it is difficult to prevent the particles from being displaced and deformed after being compressed, resulting in a significant increase in the elongation of the positive electrode sheet and poor cycle performance. The positive electrode sheet of the present application exhibits low elongation, and the lithium-ion battery exhibits excellent capacity performance and cycle performance.
[0160] The content of doping elements in the positive electrode material will usually also affect the performance of the positive electrode sheet. It can be seen from Examples 1 and 14 to 17 that, on the basis of the positive electrode material having the structural characteristics of the present application, by adjusting the content of doping elements in the positive electrode material within the scope of the present application, it is beneficial to obtain a lithium-ion battery with excellent capacity performance and cycle performance, and the elongation of the positive electrode sheet is low.
[0161] Figure 4 is the SEM image of the positive electrode material of Example 1, from Figure 4 It can be seen that the secondary particles (i.e. the large particles with darker colors in the figure, i.e. the second particles of the present application) include a plurality of fused primary particles, and the surface of the secondary particles has gaps, and the gaps are located at the fusion interfaces of the primary particles, so that the surface of the secondary particles presents a "splicing" structure; and, the surface of the secondary particles is attached with first particles with relatively small particle sizes (i.e. the small particles with brighter colors in the figure), thereby forming a two-level gradation of large and small particles with the secondary particles.
[0162] Figure 5 The SEM image of the positive electrode material of Comparative Example 1 is shown in FIG. Figure 5 It can be seen that the surfaces of its secondary particles (i.e., the large particles with darker colors in the figure) have no gaps, indicating that the primary particles used to form the secondary particles have been completely fused.
[0163] Figure 6 The SEM image of the positive electrode material of Comparative Example 2 is shown in FIG. Figure 6 It can be seen that the secondary particles have an obvious spherical structure, and the surface of the secondary particles presents a loose porous structure, which is formed by primary particles with nanometer sizes.
[0164] Figure 7 is a SEM image of the cross section of the positive electrode material layer of Example 1, from Figure 7 It can be seen that the positive electrode material layer is distributed with block-shaped second particles with larger particle sizes and solid ellipsoidal first particles, forming a two-level distribution of large and small particles.
[0165] Figure 8 This is a partial SEM enlarged view of the cross section of the positive electrode material layer of Example 1, from Figure 8 It can be seen that the secondary particle (ie, the largest particle in the figure, also the second particle of the present application) has gaps on its surface and holes inside.
[0166] Fig. 9 This is a partial SEM enlarged view of the cross section of the positive electrode material layer of Comparative Example 1, from Fig. 9 It can be seen that the secondary particle (i.e. the largest particle in the figure) is a solid structure with no gaps on the surface and no holes inside.
[0167] Fig.10 The particle size distribution diagram of the positive electrode materials of Example 1, Comparative Example 1 and Comparative Example 2 is shown in FIG. Fig.10 It can be seen that the present application adjusts the average sphericity of the second particles within the scope of the present application, so that the proportion of large particles is smaller when the positive electrode material has a higher compaction density, which is beneficial to improving the capacity performance of the lithium-ion battery.
[0168] The above is a detailed introduction to a positive electrode plate, a battery, an energy storage device and an electrical equipment disclosed in the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solutions and core inventions of the embodiments of the present application. At the same time, for those skilled in the art, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A positive electrode sheet, characterized in that: A positive electrode current collector is included, wherein at least one side of the positive electrode current collector has a positive electrode material layer, the positive electrode material layer includes a positive electrode material, and the positive electrode material includes a first particle and a second particle; The second particles are secondary particles formed by fusion of the primary particles, the surfaces of the second particles have gaps, the interiors of the second particles have holes, and the holes are connected to the outside through the gaps; The average sphericity of the second particles is S, where S≤0.
6.
2. The positive electrode sheet according to claim 1, characterized in that: 0.4≤S≤0.6。 3. The positive electrode sheet according to claim 1, characterized in that: In the cross section of the second particle, the area of the holes accounts for A in the total area of the cross section, and 10%≤A≤23%.
4. The positive electrode sheet according to claim 1, characterized in that: The second particles include a plurality of fused primary particles, and the gaps are located at fused interfaces of the primary particles.
5. The positive electrode sheet according to claim 4, characterized in that: The maximum particle size of the primary particles is D max , 1μm≤D max ≤6μm.
6. The positive electrode sheet according to claim 1, characterized in that: The positive electrode material satisfies at least one of the following characteristics: a) the Dv50 of the positive electrode material is D1, 0.8 μm≤D1≤1.3 μm; b) The compaction density of the positive electrode material is 2.5 g / cm 3 ~2.6g / cm 3 .
7. The positive electrode sheet according to claim 1, characterized in that: The first particles have a solid ellipsoidal structure.
8. The positive electrode sheet according to claim 7, characterized in that: The Dv50 of the first particles is D2, 0.2 μm≤D2≤0.5 μm.
9. The positive electrode sheet according to claim 1, characterized in that: The positive electrode material has the chemical formula LiFe x Ti y PO4 / C, x+y=1, and 0<y≤0.
05.
10. The positive electrode sheet according to claim 1, characterized in that: The elongation rate of the positive electrode sheet is 0.5% to 0.8%.
11. A battery, characterized in that: The invention comprises the positive electrode sheet as described in any one of claims 1 to 10.
12. An energy storage device, characterized in that: The invention comprises a casing and at least one battery according to claim 11, wherein the battery is accommodated in the casing.
13. An electrical equipment, characterized in that: It includes the energy storage device as described in claim 12, and the energy storage device supplies power to the electrical equipment.
Citation Information
Cited By
Positive electrode, battery, energy-storage apparatus, and electricity-consumption device
WO2026145436A1